Rethinking Knowledge from an Imitative Perspective Towards Competitive Advantage - Abdallah, Mohamad Ali Hassan (Open Science Journal, 2019)
This paper examines how imitation of knowledge could lead to competitive advantage (CA), it is based on the paradox of previous researches, where some support innovation as a process that creates a CA, where others consider imitation as the best strategy. Through these contradictions, a new concept arose and discussed “Imovation.” This study is accompanied by two empirical studies, and more practical research for the future is advised.